(untitled) (Marketing Journal, 2025)
In this article, the essence of halal standards is analyzed, the requirements established for it are studied on a scientific basis, and important socio -economic concepts are described by the author. Also, international standards developed by the Institute of Standards and Metrology for Islamic Countries (SMIIC) under the Organization of Islamic Cooperation (OIC) were studied, and requirements for categories A, B, C of accommodation facilities and catering establishments were analyzed. 46